Innovation networks on aeronautical portuguese heritage: a collaborative destination marketing approach - Palhais, R. (2020)
This study intends to develop a tourism product by adding value to Portuguese aeronautical resources, contributing to existing knowledge by: i) exploring aeronautical heritage as a collaborative destination marketing: the Portuguese Aeronautical Route (PAR); ii) developing tourism product through innovation networks. The PAR incorporates collaborative destination marketing and proposes a product that could qualify Portuguese heritage. Our findings suggest the opportunity to promote the country as an aeronautical destination brand, supported by a multi-destination route. The PAR also enables a continuous resource valorisation and ensures sustainability by involving collaboration which feeds an innovation cycle and reinforces its marketing potential.